Prophylactic Versus Extended Antibiotics Regimen in Breast Cancer Surgery - Mazin A Shakir; Husam H AliM (Diyala Journal of Medicine, 2019)
Background: A single intravenous preoperative prophylactic dose of an antibiotic with antistaphylococcal activity represent standard care for breast and axillary surgical procedures. Some surgeons also prescribe postoperative extended regimen for all patients with breast and axillary surgery to prevent infection.